2021
DOI: 10.1007/s11085-021-10036-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Total Pressure and Furnace Tube Material on the Oxidation of T22 in Humidified Air

Abstract: Oxidation of the Fe-base alloy T22 in humid air at 500 °C was investigated. The samples were exposed for up to 1000 h at 1 bar and 20 bar. The influence of three furnace tube materials, alumina, ET45 and quartz glass, on the oxide scale morphology was investigated. Samples and their cross sections were examined using optical microscopy, scanning electron microscopy, electron probe micro analysis and Raman spectroscopy. Multilayered oxide scales consisting of hematite, magnetite and Fe–Cr spinel were found on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…All exposures carried out on T22 in the absence of salt resulted in a slow-growing oxide exhibiting both similar thickness and microstructure as reported in previous studies carried out on the same alloy type in humidified air [31][32][33]. Accordingly, the microstructure analysis revealed that the oxide scale remained uniform and with no indication of spallation or crack formations regardless of exposure time.…”
Section: Oxidation Of T22 In the Absence Of Salt (Reference)supporting
confidence: 73%
“…All exposures carried out on T22 in the absence of salt resulted in a slow-growing oxide exhibiting both similar thickness and microstructure as reported in previous studies carried out on the same alloy type in humidified air [31][32][33]. Accordingly, the microstructure analysis revealed that the oxide scale remained uniform and with no indication of spallation or crack formations regardless of exposure time.…”
Section: Oxidation Of T22 In the Absence Of Salt (Reference)supporting
confidence: 73%
“…At this time, the oxide layer structure from the gas side to the substrate side is the Fe O 4 layer and FeCr 2 O 4 layer, as shown in Figure 11. Schlereth et al [34] found that T22 formed a multilayered oxide scale consisting of Fe 2 O 3 , Fe 3 O 4 and Fe-Cr spinel in humidified air at 500°C. They proposed that the composition and morphology of the oxide scales depend on the material and pressure, in which the thickness of Fe 2 O 3 decreased with increasing pressure.…”
Section: Critical Criterion Of the Formation Of Fe 2 Omentioning
confidence: 99%